STRATEGI BAURAN PEMASARAN UNTUK BISNIS JASA: BIBLIOMETRIK ANALISIS - Iklila Amiroh; Dita Rahmi; Errica Dwitanti; Bambang Supeno (ITB AAS INDONESIA Surakarta, 2022)
In finding the proper and most effective marketing plan to implement, one of the marketing mix's components can be considered. The notion of marketing is already regarded as the foundation of strategic development in every industry in the world, regardless of whether the organization operates in the sphere of products or services. The objective of this study is to provide a comprehensive analysis of marketing mix methods employed by service sector organizations from 2017 to 2021. This research literature review employs bibliometric analysis. By presenting the results of co-authorship, co-occurrence, and citation analysis, the study supported bibliometric analysis methodologies using 42 articles extracted from 50 pieces of data acquired from Google Scholar through the Publish or Perish application and VOSviewer. The finding reveals that one of the aspects that the company can observe in reaching the optimal and best marketing plan to apply is the marketing mix components. This is significant since the marketing mix is one of the most critical factors for customers when making purchasing decisions. If a company does not pay attention to what customers seek, it is almost inevitable that it will miss numerous opportunities to acquire customers and that the items offered would be wasted.